Pengaruh Ukuran Pemerintah Daerah, Jumlah SKPD, UmurPemerintah Daerah Dan Temuan Audit TerhadapTingkat Pengungkapan Laporan KeuanganPemerintah Daerah (LKPD)(Studi Empiris Lkpd Kabupaten/Kota Di Provinsi Jawa TengahTahun 2012-2014) - Ernawati, Tika, Drs. Atwal Arifin, M.Si, Ak (2016)
This study aimed to analyze the effect of the size of local government, the number of SKPD, the life of the local government, and the audit findings on the level of Laporan Keuangan Pemerintah Daerah (LKPD) (Empirical Study LKPD Regency / City in Central Java province Years 2012-2014). The population in this study were 35 districts / cities in Central Java province. The sampling technique used by the researchers is purposive sampling. This research uses a quantitative approach. The analysis used logistic regression analysis. The results of this study indicate that the variable size of the local government, the number of SKPD, and the life of local government influence on the level of disclosure LKPD. While the audit findings to the variable does not affect the disclosure LKPD.